Sphingosine kinase-2 is overexpressed in large granular lymphocyte leukemia and promotes survival through Mcl-1 - LeBlanc, Francis R (Br J Haematol, 2020)
Sphingolipid metabolism is increasingly recognized as a therapeutic target in cancer due to its regulation of cell proliferation and apoptosis. The sphingolipid rheostat is proposed to control cell fate through maintaining balance between pro-apoptotic and pro-survival sphingolipids. This balance is regulated by metabolizing enzymes involved in sphingolipid production. One such enzyme, sphingosine kinase-2 (SPHK2), produces pro-survival sphingosine 1-phosphate (S1P) by phosphorylation of pro-apoptotic sphingosine. Elevated SPHK2 has been found in multiple cancer types and contributes to cell survival, chemotherapeutic resistance and apoptosis resistance. We have previously shown elevation of S1P in large granular lymphocyte (LGL) leukemia serum and cells isolated from patients. Here, we examined SPHK2 expression in LGL leukemia and found SPHK2 mRNA and protein upregulation in a majority of LGL leukemia patient samples. Knockdown of SPHK2 with siRNA in LGL leukemia cell lines decreased proliferation. Additionally, the use of ABC294640 or K145, both SPHK2-specific inhibitors, decreased viability of LGL leukemia cell lines. ABC294640 selectively-induced apoptosis in LGL cell lines and freshly isolated LGL leukemia patient cells compared to normal controls. Mechanistically, SPHK2 inhibition downregulated pro-survival myeloid cell leukemia-1 (Mcl-1) protein through proteasomal degradation. Targeting of SPHK2 therefore provides a novel therapeutic approach for the treatment of LGL leukemia.